Implementation of Public Service Transparency Policy at the Jaya Mukti Village Office, Dumai City - Erinaldi, Erinaldi; Handayani, Fitri; Ilhamdi, Ilhamdi; Elviona, Jessyca; Tafonao, Otomosi (Global Education Journal, 2025)
Transparency of public information is an important pillar in the implementation of good governance. This study aims to analyze the implementation of public service transparency policies at the Jaya Mukti Urban Village Office in Dumai City within the framework of implementing good governance principles. This research method uses a literature review by examining various academic sources, government regulations, and empirical studies related to public service transparency at the urban village and sub-district levels in Indonesia. The results of the study indicate that, based on the results of the review, transparency is one of the main principles of good governance as regulated in Law No. 14 of 2008 concerning Public Information Disclosure, and is reinforced by its derivative policies such as Regulation of the Minister of Administrative and Bureaucratic Reform No. 15 of 2014 concerning Guidelines for Public Service Standards and Information Commission Regulation No. 1 of 2021. The results of the study indicate that transparency practices at the urban village level, including in Jaya Mukti, still face various obstacles such as limited human resources, minimal use of information technology, and low digital literacy of civil servants. However, several opportunities for strengthening can be optimized through civil servant training, development of digital-based public information systems, and increasing public participation in monitoring public services. Transparency has been proven to play a crucial role in increasing accountability, public trust, and the quality of public administration services.